Narkotika dan Ancaman Terhadap Pembangunan Bangsa Sebuah Tinjauan Politik Hukum - Telly Areska Putra; M.S Tumanggor; Joko Sriwidodo (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
The Indonesian narcotics criminal justice system has evolved from a focus on punishment to rehabilitation, driven by concerns over the high rate of drug abuse. Law No. 35 of 2009 and the 2014 Joint Regulation clarify the separation of treatment between dealers (subject to criminal sanctions) and users/addicts (prioritized by rehabilitation). This situation has naturally sparked controversy regarding the ideal legal policy/criminal law in Indonesia for addressing the problem of drug trafficking. The research method used in this study is a normative juridical research method. The materials reviewed include primary, secondary, and tertiary legal materials. The results show that law enforcement policies for drug addicts and abusers are still primarily carried out through the courts. Therefore, efforts to fulfill the rights of drug addicts and abusers (who are considered victims) in the form of rehabilitation must go through a lengthy criminal procedure. In reality, addicts and abusers who go through the criminal process generally lose interest in treating themselves, because they have the view that it is useless to treat themselves if in the end they still have to go to prison later